O utilitarismo preferencial de Peter Singer: uma abordagem ética para a defesa animal - Medeiros , Géssyca Deize Santos (2017)
In recent decades, the complex issue of defense and non-human animal rights has been emphasized. Our interest and the studies about the mentioned problematic, verify that they deserve an ethical consideration, which stimulated us to investigate its philosophical foundations. In this sense, the present research approaches the proposal of an ethics in defense of nonhuman animals from the preferential utilitarian perspective of Peter Singer. In this sense, we examined some of the conceptions that deal with human relations with other living beings, in particular, as proposed in this research, with nonhuman animals. Initially, we treated of concepts of animality and personhood as natural conditions of both species, distinctly from what traditional ethics proclaim. Subsequently, we analyzed the currents of thought by which we reflect on the relations between human beings and nonhumans in our postmodern societies, namely: anthropocentrism and speciesism, and from them, it is understood the implausibility of the exclusion of nonhuman animals of our moral community, since both are morally unjustifiable, and with this, one arrives at the sentiocentrism, a theory by which one understands the necessity of the inclusion of the other beings sensitive to the scope of our discussions and moral dilemmas. Posteriorly, we approached the conception of practical or applied ethics based on a universalizable point of view, whose pretension is the solution of moral questions and dilemmas under a practical bias of daily life. Therefore, we analyzed the definition of classic utilitarianism from the ideas of Jeremy Bentham and John Stuart Mill, as well as the utilitarianism of the preferences of Australian philosopher Peter Singer, all this with the aim of proving its impact and application in the animal liberation front. The singer's perspective proposes as a preliminary condition a discussion on the problem of equality that allows to highlight the basic moral principle of its ethical conception: the principle of equal consideration of interests. As shown, this principle holds that if there are similar interests in the plan of actions, they must be respected regardless of skin color, sexes, reasoning ability or any factual form. In a generic way, the moral idea of considering interests has as a parameter limit of sensitivity or, in specific terms, and in agreement with the classical utilitarians, the capacity to suffer or to feel pleasure. Thus, for Singer, since the sentience is satisfied, the principle of equality must also be applied to the interests of nonhuman animals. This allows us to state that human beings have duty to consider the interests of other animals impartially to the detriment of their interests as minor, since their indiscriminate exploration is unjustifiable in the scope of morality. With these considerations, in the end, we avaluated some criticisms of Singer's conception, as well as the possible answers to such controversies and misunderstandings.